Planejamento integrado de sistemas de distribuição de energia elétrica robustos com geração distribuída - Cristiane Geralda Taroco (2014)
ln this work it is developed a tool dedicated to plan electric power distribution sys- tems able to find networks that are robust, reliable and have lower monetary cost. This tool is able to perform the following operations (i) to plan the new network topology; (ii) to assign the conductor capacities and types; (iii) to locate new generation units and substations; (iv) to analyse the network robustness after the allocation of new generation units. To form this tool they were developed a local search deterministic procedure that must be aplied to the solutions round by the optimization algorithm and a procedure to locate new generation units. The local search deterministic procedure is composed of three operators: i) cost irnprovernent operator, ii) robustness improvernent operator and iii) reliability irnprovernent procedure. Some uncertain variables are considered (evolution of the load, the energy price at each node and variation of the power produced by the wind turbine), since they are required to model the system evolution at medium and long term. The main purpose of the proposed algorithm is to find a set of solutions that show a favorable trade-off with regard to cost, reliability and robustness. Mono (cost) and multiobjetive (cost and reliability) statements of the problem are considered. Wind turbines were considered as the generation units to be allocated. The results show that the proposed tool is adequate for planning distribution systems as the networks obtained are robust, reliable and have lower rnonetary cost.